25th Anniversary Article: The Evolution of Electronic Skin (E‐Skin): A Brief History, Design Considerations, and Recent Progress. (22nd October 2013) - Hammock, Mallory L.; Chortos, Alex; Tee, Benjamin C.‐K.; Tok, Jeffrey B.‐H.; Bao, Zhenan
<x xml:space="preserve">Abstract</x> Human skin is a remarkable organ. It consists of an integrated, stretchable network of sensors that relay information about tactile and thermal stimuli to the brain, allowing us to maneuver within our environment safely and effectively. Interest in large‐area networks of electronic devices inspired by human skin is motivated by the promise of creating autonomous intelligent robots and biomimetic prosthetics, among other applications. The development of electronic networks comprised of flexible, stretchable, and robust devices that are compatible with large‐area implementation and integrated with multiple functionalities is a testament to the progress in developing an electronic skin (e‐skin) akin to human skin. E‐skins are already capable of providing augmented performance over their organic counterpart, both in superior spatial resolution and thermal sensitivity. They could be further improved through the incorporation of additional functionalities (e.g., chemical and biological sensing) and desired properties (e.g., biodegradability and self‐powering). Continued rapid progress in this area is promising for the development of a fully integrated e‐skin in the near future.